Keratinous and corneous-based products towards circular bioeconomy: A research review - Giovanni Davide Barone; Irene Tagliaro; Rodrigo Oliver-Simancas; Matteo Radice; Livia M. Kalossaka; Michele Mattei; Antonino Biundo; Isabella Pisano; Amparo Jiménez-Quero (Environmental Science and Ecotechnology)
Keratins and corneous proteins are key components of biomaterials used in a wide range of applications and are potential substitutes for petrochemical-based products. Horns, hooves, feathers, claws, and similar animal tissues are abundant sources of α-keratin and corneous β-proteins, which are by-products of the food industry. Their close association with the meat industry raises environmental and ethical concerns regarding their disposal. To promote an eco-friendly and circular use of these materials in novel applications, efforts have focused on recovering these residues to develop sustainable, non-animal-related, affordable, and scalable procedures. Here, we review and examine biotechnological methods for extracting and expressing α-keratins and corneous β-proteins in microorganisms. This review highlights consolidated research trends in biomaterials, medical devices, food supplements, and packaging, demonstrating the keratin industry's potential to create innovative value-added products. Additionally, it analyzes the state of the art of related intellectual property and market size to underscore the potential within a circular bioeconomic model.